2014
DOI: 10.1111/jocn.12698
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes self‐management, depressive symptoms, metabolic control and satisfaction with quality of life over time in Chinese youth with type 1 diabetes

Abstract: The deterioration of diabetes self-management over time in youth with type 1 diabetes in China deserves nurses' careful surveillance. Clinical interventions appropriate to the Chinese culture and health care system are needed to improve self-management and depressive symptoms in Chinese youth with type 1 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 34 publications
1
35
1
1
Order By: Relevance
“…Another study showed that the HbA1c level increased in the presence of a psychiatric disorder . The present study found that young people with poor metabolic control had low levels of quality of life and high depression levels, and this result is consistent with the results of another published study . Diabetic children and adolescents present depressive symptoms and low quality of life .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another study showed that the HbA1c level increased in the presence of a psychiatric disorder . The present study found that young people with poor metabolic control had low levels of quality of life and high depression levels, and this result is consistent with the results of another published study . Diabetic children and adolescents present depressive symptoms and low quality of life .…”
Section: Discussionsupporting
confidence: 92%
“…Some cross‐sectional studies report that depressive symptoms are correlated to high HbA1c levels, and have a negative effect on the quality of life . Abolfotouh et al reported that young people with type I diabetes that had a low quality of life presented high levels of depression.…”
mentioning
confidence: 99%
“…Subscales have demonstrated acceptable reliability (Cronbach alpha 0.67–0.84; test‐retest at 2 weeks 0.77–0.85) and validity. (Guo et al ). In this study, the Cronbach alpha of the five subscales were 0.78, 0.72, 0.85, 0.82, and 0.81, respectively.…”
Section: The Studymentioning
confidence: 99%
“…Daily self‐management of type 1 diabetes is necessary to reach targets of metabolic control and improve quality of life . In Chinese youth, better diabetes self‐management has been associated with better metabolic control and quality of life . Self‐management of type 1 diabetes in children and adolescents consists of youth and their parents sharing responsibility for decisions related to the control of the disease, and maintaining health and well‐being.…”
Section: Introductionmentioning
confidence: 99%